Motorization Management in Ethiopia - Gorham, Roger (World Bank, Washington, DC, 2022)
Motorization management is the process of shaping, through public policies and programs, the profile, quality, and quantity of the motor vehicle fleet as motorization occurs. Across Africa, governments are struggling to manage the effects of rapid motorization and urbanization. In the past two decades, Africa has been the fastest urbanizing region in the world, growing at 3.44 percent on average which is much higher than the rate of other rapid developing regions, such as Asia and Latin America. Given that Africa remains the least developed region, the rapid urban growth pace will likely accelerate motorization development and challenge the limited resource base to meet the demand of the growing urban populations. While this motorization potentially means that more African people will be able to claim the benefits of improved access to opportunities and mobility, it raises alarming questions about the sustainability of this future. Will countries be able to build and maintain infrastructure to accommodate these vehicles Will the quality of the vehicles support African development goals and the region’s ability to meet the Sustainable Development Goals and climate obligations This report lays out plausible motorization policies that can be implemented by the government of Ethiopia.